2004
DOI: 10.1016/j.virol.2004.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Towards a molecular identification and classification system of lepidopteran-specific baculoviruses

Abstract: Virus genomics provides novel approaches for virus identification and classification. Based on the comparative analyses of sequenced lepidopteran-specific baculovirus genomes, degenerate oligonucleotides were developed that allow the specific amplification of several regions of the genome using polymerase chain reaction (PCR) followed by DNA sequencing. The DNA sequences within the coding regions of three highly conserved genes, namely polyhedrin/granulin (polh/gran), late expression factor 8 (lef-8), and late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 34 publications
4
91
0
5
Order By: Relevance
“…The Lepidopteran NPVs were separated into two groups, group I and II, based on the conserved gene, polyhedron, which encoded the major occlusion body protein required for producing viral progeny 3,5 . Later, the phylogenetics of NPVs were generated with other conserved genes, www.scienceasia.org for example lef-2 33 , lef-8, lef-9 34,35 , and ecdysteroid UBP-glycosyl transferase (egt) 4 . Recently, many phylogenetics of NPVs have been established by means of the combination of several conserved gene sequences and whole genome sequences 7,36,37 .…”
Section: Phylogenetic Analysis Of Group Imentioning
confidence: 99%
See 1 more Smart Citation
“…The Lepidopteran NPVs were separated into two groups, group I and II, based on the conserved gene, polyhedron, which encoded the major occlusion body protein required for producing viral progeny 3,5 . Later, the phylogenetics of NPVs were generated with other conserved genes, www.scienceasia.org for example lef-2 33 , lef-8, lef-9 34,35 , and ecdysteroid UBP-glycosyl transferase (egt) 4 . Recently, many phylogenetics of NPVs have been established by means of the combination of several conserved gene sequences and whole genome sequences 7,36,37 .…”
Section: Phylogenetic Analysis Of Group Imentioning
confidence: 99%
“…These phylogenetic trees were suggested to be more acceptable than those constructed by a single gene. However, the tree constructed by a single gene had been used for quick identification 34 . In this work, even though ie-1 gene was poorly conserved, the pattern of the tree topology derived from IE-1 amino acid sequences agreed with those of other tree topologies based on single highly conserved genes, the combination of highly conserved genes, and complete genome sequences.…”
Section: Phylogenetic Analysis Of Group Imentioning
confidence: 99%
“…In fact, a low level of idendity can be expected between SpliNPV-TR1 and NPVs isolated from different host families except Noctuidae and this would have not constituted a surprising situation. Lange et al (2004) reported that group II NPVs presently subsume all lepidopteran-specific NPVs not belonging to the monophyletic group I NPVs and the distribution of the virus host families so far suggests a strong coevolution between baculoviruses and insect host families. Herniou et al (2001) also reported that monophyly of the group II NPVs is far less well supported that that for the group I NPVs or the GVs.…”
Section: Splinpv-tr1mentioning
confidence: 99%
“…The virions are occluded in a polyhedral shaped occlusion body called polyhedra in the NPV genus and are protected against enviromental conditions for years (Toprak et al 2005a). About 600 baculoviruses are described to infect insects that belong mostly to the insect orders Lepidoptera, Hymenoptera, and Diptera (Martignoni and Iwai 1981) and about 90 % were reported from 34 different families of Lepidoptera (Lange et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…The BmNPV polyhedrin gene is non-essential late gene for BmNPV replication and the ORF contains 738 nucleotides 6 . The polh gene has not only been used in phylogenetic studies but also in the molecular identification of baculoviruses specific to lepidoptera [7][8][9][10] . Baculovirus-repeated ORFs (bro) are widespread among invertebrate viruses.…”
Section: Introductionmentioning
confidence: 99%